Feeling safe again: Recovering from property crime - Baker, David (The Australia Institute, 2014)
Property crime in Australia declined by more than half between 2001 and 2011 – affecting 2.9 per cent of households in 2012. Although the proportion of victims has been falling steadily, recovery from these incidents remains an important policy issue. Until the mid 1980s it had long been accepted that victims of burglary recovered within two or three months. More recent studies, however, have found recovery can take much longer. This paper analyses reported feelings of safety of victims of property crime in 2010, comparing these feelings with those who were not victims. There was no notable change in average safety scores in the following two years for either group. The paper suggests that greater support is needed to assist people who are victims of property crime to access social support to aid their recovery.
Policy Brief No.66
Keywords: Social Capital -- Social support; Stress -- Life events; Life Events -- Crime; Disadvantage, adversity and resilience; Life Events; Stress; Social Capital; Social support; Crime; Life events; Adversity and resilience; Dsiadvantage, adversity and resilience